Pendampingan Pembelajaran Al-Qur’an di TPA Ummul Qura’ Tangerang Selatan - rizkia, annisa; Mubarak, Muhammad Zacky; Abdullah, Abdullah; Anas, Muhammad; Suparno, Darsita (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2026)
This community service activity focuses on mentoring Quran learning at Ummul Qura Quranic Education Center in South Tangerang in response to the low quality of students’ Quran reading skills. The main issues identified include limited accuracy in pronouncing Arabic letters, inadequate application of basic recitation rules, and low reading fluency caused by limited learning time and insufficient individual guidance. The purpose of this activity is to improve students’ Quran reading ability through a structured and participatory learning assistance program. The method applied is participatory mentoring based on direct practice, emphasizing guided reading, repeated practice, and immediate correction. The activity was implemented through several stages, including initial assessment of students’ reading abilities, continuous mentoring sessions, and regular evaluation of learning progress. The results of the community service indicate a positive improvement in students’ Quran reading skills, particularly in pronunciation accuracy, application of basic recitation rules, and reading fluency. In addition to technical improvements, students showed increased confidence and motivation in learning the Quran. The mentoring process also strengthened the role of teachers in providing individual guidance and fostering a more active and supportive learning environment. Overall, this mentoring program contributes to improving the quality of Quran learning in nonformal religious education institutions and has the potential to be replicated in similar educational settings. ABSTRAK Kegiatan pengabdian kepada masyarakat ini berfokus pada pendampingan pembelajaran Al-Qur’an di TPA Ummul Qura Tangerang Selatan sebagai respons terhadap rendahnya kualitas kemampuan membaca Al-Qur’an santri. Permasalahan yang dihadapi meliputi ketidaktepatan pelafalan huruf hijaiyah, lemahnya penerapan kaidah bacaan dasar, serta rendahnya kelancaran membaca akibat keterbatasan waktu pembelajaran dan pendampingan individual. Tujuan kegiatan ini adalah meningkatkan kemampuan membaca Al-Qur’an santri melalui program pendampingan pembelajaran yang terstruktur dan partisipatif. Metode yang digunakan adalah pendampingan berbasis praktik langsung dengan menekankan latihan membaca terbimbing, pengulangan bacaan, dan koreksi secara berkelanjutan. Pelaksanaan kegiatan dilakukan melalui tahapan asesmen awal kemampuan membaca, pendampingan pembelajaran secara intensif, serta evaluasi perkembangan santri secara berkala. Hasil kegiatan menunjukkan adanya peningkatan kemampuan membaca Al-Qur’an santri, khususnya pada aspek ketepatan pelafalan huruf, penerapan kaidah bacaan dasar, dan kelancaran membaca. Selain itu, pendampingan juga berdampak pada meningkatnya kepercayaan diri dan motivasi belajar santri serta menguatnya peran pengajar dalam proses pembelajaran. Dengan demikian, pendampingan pembelajaran Al-Qur’an ini berkontribusi dalam meningkatkan mutu pembelajaran Al-Qur’an pada lembaga pendidikan nonformal dan berpotensi untuk diterapkan pada TPA lain dengan karakteristik serupa.